Penggunaan Sistem Informasi Geografis untuk Menghitung Dimensi Lumpur Panas di Porong, Sidoarjo - Pramono, Gatot H.; Sardjono, Seno P. (Forum Geografi, 2007)
The hot mud extrusion in Porong, Sidoarjo since May 29, 2006 has impacted many aspects includingÂ social, culture, economy and transportation. Several weeks later, a collaborative team was formed to investigate theÂ factors controlling the hot mud extrusions. One important aspect is concerning the mud dimensions such as its perimeter, area, volume and discharge. Bakosurtanal was assigned to carry out this task. Field surveys to acquire the mud heights were conducted twice within one month interval. Geographic Information System (GIS) using 3 dimentional approach was employed to compute the mud dimesions. One of the results show that the mud discharge is about 50.000 m3/day. This value was later commonly used to refer the magnitude of the hot mud.